Vitamin C supplementation does not improve hypoxia-induced erythropoiesis (2012)
Martinez-Bello,Vladimir E., Fabian Sanchis-Gomar, Daniel Martinez-Bello, Gloria Olaso-Gonzalez, Mari Carmen Gomez-Cabrera, and Jose Viña. Vitamin C Supplementation Does Not Improve Hypoxia-Induced Erythropoiesis. High Alt Med Biol 13:269-274, 2012. - Hypoxia induces reactive oxygen species production. Supplements with antioxidant mixtures can compensate for the decline in red cell membrane stability following intermittent hypobaric hypoxia by decreasing protein and lipid oxidation. We aimed to determine whether supplementation with vitamin C is implicated in the regulation of erythropoiesis and in the oxygen-carrying capacity of the blood, and also whether antioxidant supplementation prevents the oxidative stress associated to intermittent hypoxia. Twenty-four male Wistar rats were randomly divided into four experimental groups: normoxia control (n=6), normoxia + vitamin C (n=6), hypoxia control (12 h pO2 12%/12 h pO2 21%) (n=6), and hypoxia + vitamin C (n=6). Animals were supplemented with vitamin C at a dose of 250 mg kg-1 day-1 for 21 days. Red blood cell count, hemoglobin, hematocrit, reticulocytes, erythropoietin, and oxidative stress parameters such as malondialdehyde and protein oxidation in plasma were analyzed at two different time points: basal sample (day zero) and final sample (day 21). Similar RBC, Hb, Hct, and Epo increments were observed in both hypoxic groups regardless of the vitamin C supplementation. There was no change on MDA levels after intermittent hypoxic exposure in any experimental group. However, we found an increase in plasma protein oxidation in both hypoxic groups. Vitamin C does not affect erythropoiesis and protein oxidation in rats submitted to intermittent hypoxic exposure. © Copyright 2012, Mary Ann Liebert, Inc. 2012.